2014
DOI: 10.1007/s10886-014-0517-y
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Feeding Stimulation to Protect Crops Against Insect Pests?

Abstract: Enhancing natural mechanisms of plant defense against herbivores is one of the possible strategies to protect cultivated species against insect pests. Host plant feeding stimulation, which results from phagostimulant and phagodeterrent effects of both primary and secondary metabolites, could play a key role in levels of damage caused to crop plants. We tested this hypothesis by comparing the feeding intensity of the pollen beetle Meligethes aeneus on six oilseed rape (Brassica napus) genotypes in a feeding exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 70 publications
4
37
2
Order By: Relevance
“…However, serine and especially sucrose-a well-known highly stimulant sugar (Chapman 2003)-are good candidates for further behavioural studies. Noticeably, glucosinolates did not seem to exert any major influence on pollen beetle feeding preference (Hervé et al 2014).…”
Section: Food Host-plant Acceptance (Short Range/contact Cues)mentioning
confidence: 93%
See 1 more Smart Citation
“…However, serine and especially sucrose-a well-known highly stimulant sugar (Chapman 2003)-are good candidates for further behavioural studies. Noticeably, glucosinolates did not seem to exert any major influence on pollen beetle feeding preference (Hervé et al 2014).…”
Section: Food Host-plant Acceptance (Short Range/contact Cues)mentioning
confidence: 93%
“…Indeed, Charpentier (1985) found differences between host-plant feeding preferences of pollen beetles and concluded that chemical stimuli were the most important. Hervé et al (2014) studied these stimuli by comparing six OSR genotypes for pollen beetle feeding preference, and identified possible phagostimulant/deterrent compounds in the bud perianth (the tissue that has to be pierced to access the food source) and in anthers (the tissue containing the food source). It was shown that only the composition of the perianth correlated with feeding damage, suggesting that this tissue is determinant in host-plant acceptance (Hervé et al 2014).…”
Section: Food Host-plant Acceptance (Short Range/contact Cues)mentioning
confidence: 99%
“…This suggests that CMS cultivars may be more tolerant to pollen beetle, although this has not been tested. Hervé et al (2014a) identified compounds from the bud perianth, including sucrose, proline and serine that appear to act as key feeding stimulants for pollen beetles; perianth content of these compounds varied among genotypes leading to the suggestion that OSR cultivars with reduced perianth content of these compounds, in particular sucrose, could be selected to reduce damage by the pest. Furthermore, the amount of food eaten by female pollen beetles was positively related to egg numbers and size (Hervé et al 2014b), suggesting that fewer and/or smaller eggs would also be laid on these cultivars.…”
Section: Cultivarmentioning
confidence: 99%
“…At the within-field scale, however, appropriate crop management also provides opportunities to improve beetle control, as crop management factors may affect plant growth and phenology (Valantin-Morison et al 2007), which in turn influence resource quality. As specific plant quality characteristics, for example relating to bud size or glucosinolate content, are known to play a role in pollen beetle host plant selection (Nilsson 1994;Cook et al 2006;Valantin-Morison et al 2007;Hervé et al 2014a), resource quality-mediated crop management effects are likely to influence pollen beetle abundance and damage in the field. Besides these effects, crop management is also likely to influence insect populations through microclimatic effects, and through variations in plant architecture, which may alter oviposition behaviour and food-seeking efficiency (Valantin-Morison et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Signaling effects of herbicides or their derivatives can affect biochemical traits (carbon and nitrogen metabolites, sulfur metabolites, stress defence metabolites, secondary metabolites) and growth traits (root growth rate, lateral root formation, leaf elongation) that can have considerable impact on plant-rhizosphere-soil interactions (Philippot and Hallin, 2011), plant-phyllosphere-atmosphere interactions (Bringel and Couée, 2015) or plant-herbivory interactions (Hervé et al, 2014;Savary-Auzeloux et al, 2003). These effects can occur on plant species of outstanding ecosystemic importance, such as perennial ryegrass (Serra et al, 2015a), a major component of grazed pastures and grasslands that cover over 40% of Earth's land surface area (Barbehenn et al, 2004), or rice (Zhou et al, 2015), with a global harvested area of 14% of Earth's arable land (Philippot and Hallin, 2011).…”
Section: Importance Of Herbicide-related Signaling In the Framework Omentioning
confidence: 99%